2022
DOI: 10.3390/antiox11081532
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Cellular Uptake of Exogenous Coenzyme Q10 into Human Skin Cells by X-ray Fluorescence Imaging

Abstract: X-ray fluorescence (XRF) imaging is a highly sensitive non-invasive imaging method for detection of small element quantities in objects, from human-sized scales down to single-cell organelles, using various X-ray beam sizes. Our aim was to investigate the cellular uptake and distribution of Q10, a highly conserved coenzyme with antioxidant and bioenergetic properties. Q10 was labeled with iodine (I2-Q10) and individual primary human skin cells were scanned with nano-focused beams. Distribution of I2-Q10 molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…As mentioned above, XFI offers high spatial resolution, determined solely by the applied X-ray beam diameter, and at the same time high sensitivity 8 13 , 17 , i.e., the quantitative detection of small numbers of localized cells. Unlike commonly used modalities such as Optical Imaging (OI), e.g., Bioluminescence Imaging (BLI), XFI can be used to probe deep into tissue as hard X-ray photons are much less affected by attenuation or scattering than optical photons.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…As mentioned above, XFI offers high spatial resolution, determined solely by the applied X-ray beam diameter, and at the same time high sensitivity 8 13 , 17 , i.e., the quantitative detection of small numbers of localized cells. Unlike commonly used modalities such as Optical Imaging (OI), e.g., Bioluminescence Imaging (BLI), XFI can be used to probe deep into tissue as hard X-ray photons are much less affected by attenuation or scattering than optical photons.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it is explicitly suited for longitudinal studies as the non-radioactive fluorescence markers do not decay over time such as in Positron Emission-Tomography (PET) or Single-Photon Emission Computed Tomography (SPECT) 18 . In order to make biological or medical agents visible in XFI, either molecular tracers or nanoparticles can be used for labelling 8 13 , 17 , 19 . Although Magnetic Resonance Imaging (MRI) can also be performed for multi-tracking of several different markers, MRI can, unlike XFI, only be used with specific isotopes with magnetic moments and under sophisticated setups 20 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors found exogenous I 2 -Q 10 to distribute homogeneously over the keratinocyte cell, but co-localization with subcellular organelles, such as mitochondria, was not determined. Beyond the confirmation that CoQ 10 is taken up by human keratinocytes, these data suggest a potential way to assess CoQ 10 distribution using I 2 -Q 10 in X-ray fluorescence imaging [137]. The technique was demonstrated to allow for quantitative analysis with no phenotypic changes due to the iodine labeling, and it shows promise in the investigation of mechanisms underlying exogenous CoQ uptake.…”
Section: Human Dermal Cellsmentioning
confidence: 89%
“…Keratinocytes have proved useful in the characterization of a new iodine-labeled CoQ derivative that may allow monitoring of the biodistribution of exogenous CoQ [137]. The novel iodine-labeled CoQ 10 (I 2 -Q 10 ) consists of CoQ 10 with two iodine atoms replacing the terminal carbon of the polyisoprenyl tail.…”
Section: Human Dermal Cellsmentioning
confidence: 99%